Foreign Language Anxiety in the Era of Educational Reform: A Mixed-Method Study of English Learning in Indonesian Secondary Schools - Permatasari, Amaliya Indah (English Education:Journal of English Teaching and Research, 2025)
This study investigates the levels and contributing factors of Foreign Language Anxiety (FLA) among eighth-grade junior high school students within the Kurikulum Merdeka. Employing a mixed-methods explanatory design, it combines quantitative data from the Foreign Language Classroom Anxiety Scale (FLCAS) administered to 30 students and qualitative insights from semi-structured interviews with six participants representing different anxiety levels. The findings reveal that most students experience moderate anxiety shaped by communication apprehension, fear of negative evaluation, test-related concerns, and classroom dynamics, which are further influenced by social pressure, teacher and peer evaluation, and low self-confidence. Coping strategies vary across students, ranging from independent preparation and consistent practice to relaxation, informal exposure, and positive self-talk. While the Kurikulum Merdeka promotes flexibility and participatory learning, students still encounter pressure to perform linguistically in front of peers when using English. This study advances the understanding of FLA in secondary education by highlighting its manifestations in the context of a national curriculum reform and offering practical guidance for educators and policymakers to design adaptive, inclusive, and empowering English language learning environments.